THE EFFECT OF DELIGNIFICATIONâS PARAMETERS ON CELLULASE ACTIVITY BY SOLID STATE FERMENTATION - Nyoman Moza Mardika W, Ni
Cellulase enzyme is a complex enzyme that acts synergistically to convert cellulose into simpler sugar. It is the third largest enzyme after amilase and protease due to its application in many industries such as biorefineries, pulp and paper, and textile. As cellulase has a significant role in biorefinery, optimizing cellulase production is important. One of the ways to optimize cellulase production is at its pre-treatment by delignification. Delignification will reduce lignin in lignocellulose biomass so microorganisms can easily access cellulose and produce cellulase. The most used delignification process, known for its big yield, is alkaline-thermal delignification. This study aims to see the effect of delignification’s parameters on bulk cellulase activity. These parameters include concentration of alkaline solution, duration, and temperature of delignification. Fermentation is conducted by solid state fermentation using empty fruit bunches (EFB) as substrate and Trichoderma viride as microorganism. Fermentation is conducted in 250 mL Erlenmeyer flasks. Delignification process is conducted with NaOH solution in an autoclave hydrothermal with variations of NaOH’s concentration (2%, 6%, m/v), duration (60 minutes, 80 minutes), and temperature (145?, 165?). The results showed that delignification duration and NaOH’s concentration increased cellulase activity. On the contrary, higher temperature decreased cellulase activity. Based on ANOVA, the most significant parameters were delignification duration and the three parameters’ interaction. Moreover, delignification could increase cellulase activity and accelerate the duration to gain the most optimum cellulase activity. Keywords: Enzyme activity, autoclave, parameter of delignification, cellulase, SSF